The Nonaspanins TM9SF2 and TM9SF4 Regulate the Plasma Membrane Localization and Signalling Activity of the Peptidoglycan Recognition Protein PGRP-LC in Drosophila. - Perrin, J.; Mortier, M.; Jacomin, A.C.; Viargues, P.; Thevenon, D.; Fauvarque, M.O. (Journal of innate immunity, 2015)
Transmembrane 9 (TM9) proteins, or nonaspanins, are a family of proteins conserved throughout evolution and characterized by 9 transmembrane domains. In Drosophila, TM9 superfamily protein member 4 (TM9SF4) and its closest paralogue, TM9SF2, contribute to phagocytosis of various types of particles, while TM9SF4 displays non-redundant requirement in Gram-negative bacteria engulfment. In addition, the two TM9 proteins control the actin cytoskeleton in larval haemocytes and in Drosophila S2 cells. Here, we show that TM9SF4 and TM9SF2 co-immunoprecipitate with the peptidoglycan recognition protein (PGRP)-LC, which triggers the Drosophila immune response to bacterial infection. Furthermore, both TM9 proteins co-localize with this receptor in intracellular vesicles and at the plasma membrane in Drosophila S2 cells in culture and in the fly fat body. Silencing TM9SF4 prevents plasma membrane localization of PGRP-LC, whereas silencing TM9SF2 does not, which may account for the non-redundant role of TM9SF4 in phagocytosis of Gram-negative bacteria. Finally, we provide a set of data suggesting that TM9 proteins can prevent inappropriate signalling from the unstimulated receptor. © 2014 S. Karger AG, Basel.